A preparation method of water-soluble indium copper sulfide quantum dots and its application in copper ion detection
By using raw materials such as copper nitrate, indium nitrate and thiourea, combined with the stabilizer of sodium sulfide and thiourea, water-soluble indium sulfide copper quantum dots with low toxicity and high fluorescent quantum yield are prepared, which solves the problems of toxic raw materials and low fluorescent quantum yield in the prior art, and achieves efficient copper ion detection.
Patent Information
- Application Number
- CN202311259597.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-27
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2043-09-27
AI Technical Summary
In the prior art, when synthesizing indium sulfide copper quantum dots, the raw materials used, such as thiol propionic acid, contain thiol groups, resulting in the release of toxic gases during the synthesis process, which is harmful to the human body, and has a low fluorescence quantum yield.
Water-soluble indium sulfide copper quantum dots were prepared by adjusting the reaction conditions and adding sodium sulfide as raw materials. In this method, thiourea is a stabilizer and does not contain thiol groups, which avoids the generation of toxic gases, and improves the fluorescence quantum yield of quantum dots by controlling the reaction temperature and time.
The prepared copper indium sulfide has low toxicity, fluorescent quantum yield reaches 10.05%, and has good water solubility and stability. It is suitable for copper ion detection, with high sensitivity and low detection limit.
Smart Images

Figure CN117327484B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a preparation method of water-soluble indium copper sulfide quantum dots and application thereof in copper ion detection, belonging to the technical field of fluorescent materials. Background Art
[0002] Fluorescence analysis is used to detect Cu in water due to its high sensitivity, rapidity and simplicity. 2+Concentration. Fluorescence response quantum dots are semiconductor nanomaterials with excellent optical properties. Indium copper sulfide quantum dots have received extensive attention in fluorescence analysis because of their lack of heavy metal elements, photostability, excellent surface chemical properties and ligand binding ability. In the prior art, the method for synthesizing indium copper sulfide quantum dots is thermal decomposition. For example, Riccardo Marin et al. synthesized CuInS2 quantum dots by thermal decomposition of mercaptopropyltrimethoxysilane (MPTS) [see Riccardo Marin, Alvise Vivian, Artiom Skripka, et al. Mercaptosilane-Passivated CuInS2 Quantum Dots for Luminescence Thermometry and Luminescent Labels. ACS Appl. Nano Mater. 2019, 2, 2426-2436]. Hot injection method, Liu et al. synthesized CuInS2 quantum dots with adjustable structure and band gap by changing the dose of oleylamine (OAm) and combining hot injection method [see Liwang Liu, Hong Lia, Zirui Liu, et al. Structure and band gaptunable CuInS2 nanocrystal synthesized by hot-injection method with altering the dose of oleylamine. Materials and Design 149 (2018) 145–152]. Solvothermal method, Yue et al. used 4-bromobenzenethiol (HSPh) as a reducing agent and encapsulating ligand to synthesize 2-4 nm CuInS2 quantum dots by solvothermal method [see Yue W, Han S, Peng R, et al. CuInS2 quantum dots synthesized by a solvothermal route and their application as effective electron acceptors for hybrid solar cells [J]. J. Mater. Chem., 2010, 20: 7570-7578]. Using the hydrothermal method, Liu et al. used mercaptopropionic acid (MPA) as a stabilizer to prepare water-soluble high-quality ternary CuInS2 quantum dots (QDs). The size distribution of the CuInS2 quantum dots was relatively uniform, and the particle size of most CuInS2 quantum dots was around 2 nm.[Siyu Liu, Hao Zhang, Yu Qiao, et al. One-pot synthesis of ternary CuInS2 quantum dots with near-infrared fluorescence in aqueous solution. RSC Advances, 2012, 2, 819–825]. The above method belongs to the aqueous phase method, but the raw materials for preparing CuInS2 quantum dots by the aqueous phase method are mostly amphiphilic molecules containing thiol groups, such as mercaptopropionic acid, thioglycolic acid, etc. These small molecules containing thiol groups have a strong pungent odor and release toxic gases during the synthesis process, which are harmful to the human body, and the fluorescence quantum yield of the prepared CuInS2 quantum dots is low. Therefore, it is urgent to provide a method for preparing CuInS2 quantum dots with low toxicity and high fluorescence quantum yield. Summary of the invention
[0003] The object of the present invention is to provide a method for preparing water-soluble indium copper sulfide quantum dots. The prepared indium copper sulfide quantum dots have low toxicity and high fluorescence quantum yield.
[0004] The present invention also aims to provide an application of water-soluble indium copper sulfide quantum dots.
[0005] The object of the present invention is achieved in this way. A method for preparing water-soluble indium copper sulfide quantum dots comprises the following steps:
[0006] (1) adding copper nitrate, indium nitrate and thiourea into a reaction container, adding water into the reaction container, and adding sodium sulfide after dissolution to obtain a first solution;
[0007] (2) adjusting the pH of the obtained first solution to 7-11 to obtain a second solution, which is then transferred into a reaction kettle;
[0008] (3) placing the reaction kettle in a preheated air drying oven, reacting at 130-180° C. for 2-12 hours, and naturally cooling to room temperature to obtain a third solution;
[0009] (4) filtering impurities in the third solution through a filter membrane to obtain an indium copper sulfide quantum dot solution;
[0010] (5) adding anhydrous ethanol to the indium copper sulfide quantum dot solution to generate a precipitate, and drying the precipitate to obtain indium copper sulfide quantum dots.
[0011] As an implementation method, the molar ratio of copper nitrate, indium nitrate and sodium sulfide in step (1) of the present invention is 1: (4.5-6.5): (15-19).
[0012] As an implementation method, the molar ratio of copper nitrate to thiourea in step (1) of the present invention is 1:25.
[0013] As an implementation method, the molar ratio of copper nitrate, indium nitrate, sodium sulfide and thiourea in step (1) of the present invention is 1:5.5:18:25.
[0014] As an implementation method, the pH of the second solution in step (2) of the present invention is 9.
[0015] As an implementation method, in step (3) of the present invention, the reaction temperature of the second solution in the reactor is 170° C., and the reaction time is 10 hours.
[0016] As an implementation method, the indium copper sulfide quantum dots described in the present invention are a mixture of two crystal forms: chalcopyrite and wurtzite.
[0017] The preparation process of the indium copper sulfide quantum dots of the present invention is described in detail below.
[0018] Step (1) adding copper nitrate, indium nitrate and thiourea into a reaction container, adding water into the reaction container, stirring and dissolving, then adding sodium sulfide, stirring and fully dissolving, to obtain a first solution;
[0019] Among them, the copper nitrate used is Cu(NO3)2·H2O, the indium nitrate is In(NO3)3·xH2O, the thiourea is CH4N2S, and the sodium sulfide is Na2S·9H2O.
[0020] In the present invention, the molar ratio of copper nitrate, indium nitrate and sodium sulfide is 1:(4.5-6.5):(15-19), and the molar ratio of copper nitrate, indium nitrate and sodium sulfide can be set and changed as needed, for example, the molar ratio of copper nitrate, indium nitrate and sodium sulfide is 1:4.5:15, 1:5.5:18 or 1:5.5:19, etc., which is not specifically limited. The molar ratio of copper nitrate to thiourea is 1:25. Correspondingly, the molar ratio of copper nitrate, indium nitrate, sodium sulfide and thiourea is 1:4.5:15:25, 1:5.5:18:25 or 1:5.5:19:25, etc.
[0021] Step (2) adjusting the pH of the obtained first solution to 7-11 to obtain a second solution, which is then transferred into a reaction kettle;
[0022] In this step, 0.1 mol / L dilute hydrochloric acid can be used to adjust the pH of the first solution to 7 to 11. For example, the pH of the first solution is adjusted to 7, 8, 9, 10 or 11. In the specific embodiment of the present invention, only the pH of the first solution is adjusted to 9 as an example. In addition, the reactor used in the present invention is a high-pressure reactor.
[0023] Step (3) placing the reaction kettle in a preheated air drying oven, reacting at 130-180° C. for 2-12 hours, and then naturally cooling to room temperature to obtain a third solution;
[0024] The reaction temperature may be 130° C., 140° C., 150° C., 160° C., 170° C. or 180° C., and in the specific embodiment of the present invention, the reaction temperature is only 170° C. for example. Similarly, the reaction time may be 2 hours, 4 hours, 6 hours, 8 hours, 10 hours or 12 hours, and in the specific embodiment of the present invention, the reaction time is only 10 hours for example.
[0025] Step (4) filtering impurities in the third solution through a filter membrane to obtain an indium copper sulfide quantum dot solution. The filtering method may also be other methods.
[0026] Step (5) adding anhydrous ethanol to the indium copper sulfide quantum dot solution to generate a precipitate, and drying the precipitate to obtain indium copper sulfide quantum dots;
[0027] In this step, anhydrous ethanol is added to the indium copper sulfide quantum dot solution to generate a precipitate, and the precipitate is dried at a certain temperature for a period of time, for example, at a temperature of 50 to 55° C. for 20 to 24 hours to obtain indium copper sulfide quantum dots.
[0028] The indium copper sulfide quantum dots prepared by the present invention have a maximum excitation wavelength of 467 nm, a maximum emission wavelength of 658 nm, a fluorescence quantum yield of 10.05%, an average particle size of 2.88±0.05 nm, and are a mixture of two crystal forms of chalcopyrite and wurtzite.
[0029] The fluorescence quantum yield is calculated as follows:
[0030] The fluorescence quantum yield of water-soluble indium copper sulfide quantum dots was measured by dilute solution fluorescence reference method, and the specific steps were as follows:
[0031] (1) Rhodamine 6G is selected as a standard substance for reference (dissolved in an ethanol solution), and its fluorescence quantum yield is 95.0%. The Rhodamine 6G solution and the CuInS2 quantum dot solution are diluted to an absorbance of less than 0.05. The CuInS2 quantum dot solution is the solution obtained in step 104.
[0032] (2) The fluorescence spectra of Rhodamine 6G solution and CuInS2 quantum dot solution were measured at 470 nm respectively.
[0033] (3) Calculate the fluorescence integrated area and substitute it into formula 1 to calculate the fluorescence quantum yield.
[0034]
[0035] in, represents the fluorescence quantum yield of CuInS2 quantum dots, represents the fluorescence quantum yield of the reference substance, F represents the fluorescence integrated area of CuInS2 quantum dots, and F s represents the fluorescence integrated area of the reference substance, A represents the absorbance of CuInS2 quantum dots, and A s represents the absorbance of the reference substance, n represents the refractive index of water, n s represents the refractive index of ethanol.
[0036] The present invention also provides an application of water-soluble indium copper sulfide quantum dots in copper ion detection.
[0037] The prepared indium copper sulfide quantum dots can be used as fluorescent probes to specifically recognize metal ions Cu 2+ , Indium copper sulfide quantum dots emit red light under 365nm excitation, Cu 2+ The fluorescence of indium copper sulfide quantum dots is quenched and shows a certain linear relationship: the fluorescence intensity of indium copper sulfide quantum dots increases with Cu 2+ Therefore, the fluorescence spectrum of indium copper sulfide quantum dots was measured in aqueous solution as a fluorescent probe, and the change of fluorescence intensity can be used to detect Cu 2+ The qualitative or quantitative detection has the advantages of high sensitivity, rapidity, simplicity and low detection limit, among which the detection limit can reach 23nmol / L.
[0038] The positive effects achieved by the present invention are: the preparation method of the present invention adopts thiourea as a stabilizer, and thiourea does not contain a thiol group. Compared with the indium copper sulfide quantum dots synthesized by mercaptopropionic acid, thioglycolic acid and the like as stabilizers, the prepared indium copper sulfide quantum dots have low toxicity. And the -NH2 functional group in thiourea combines with the indium copper sulfide quantum dots, which increases the stability and dispersibility of the indium copper sulfide quantum dots, and the fluorescence quantum yield of the prepared indium copper sulfide quantum dots reaches 10.05%. The preparation method of the present invention is simple to operate, the raw materials are easy to obtain, the conditions are mild, and the prepared CuInS2 quantum dots have good water solubility, excellent fluorescence performance and good stability. It is used as a fluorescent probe for copper ion detection, and has the advantages of high sensitivity, high selectivity, simplicity, and low detection limit. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Figure 1 The present invention is a flow chart of a method for preparing water-soluble indium copper sulfide quantum dots.
[0040] Figure 2 This is the X-ray diffraction pattern of the CuInS2 quantum dots prepared in Examples 1 to 5.
[0041] Figure 3This is a transmission electron microscope image of the CuInS2 quantum dots prepared in Example 3.
[0042] Figure 4 This is the infrared spectrum of the CuInS2 quantum dots prepared in Example 3.
[0043] Figure 5 This is the X-ray diffraction pattern of the CuInS2 quantum dots prepared in Example 3.
[0044] Figure 6 It is the ultraviolet-visible absorption, excitation and emission spectra of the CuInS2 quantum dots prepared in Example 3.
[0045] Figure 7 This is the X-ray photoelectron spectrum of the CuInS2 quantum dots prepared in Example 3.
[0046] Figure 8 It is a bar graph of the fluorescence intensity ratio when different metal ions are added to the CuInS2 quantum dot solution.
[0047] Fig. 9 In CuInS2 quantum dots-Cu 2+ Histogram of the fluorescence intensity ratio when different metal ions are added to the system.
[0048] Fig.10 Under the excitation wavelength of 468nm, different concentrations of Cu were added to the CuInS2 quantum dot solution. 2+ Fluorescence spectrum of .
[0049] Fig.11 CuInS2 quantum dot solution in different Cu 2+ Line graph of fluorescence intensity ratio at different concentrations. DETAILED DESCRIPTION
[0050] The following examples serve to illustrate the invention.
[0051] It should be noted that in the following specific examples, the operations involved, if the conditions are not specified, are all carried out under conventional conditions or conditions recommended by the manufacturer. The raw materials used, if the manufacturers and specifications are not specified, are all conventional products that can be obtained through commercial purchase.
[0052] Example 1 Preparation of water-soluble indium copper sulfide quantum dots
[0053] Step (1) Add 0.0116 g Cu(NO3)2·H2O, 0.063 g In(NO3)3·xH2O and 0.0913 g CH4N2S into a beaker, add 60 mL deionized water, add 0.2036 g Na2S·9H2O after fully dissolving, so that the molar ratio of copper source, indium source and sulfur source is 1:4.5:18, and stir evenly to obtain a dark red solution.
[0054] Step (2) The pH of the solution obtained in step (1) was adjusted to 9 with a 0.1 mol / L HCL dilute solution and stirred at room temperature for 30 min.
[0055] Step (3) The solution obtained in step (2) was transferred into a 100 mL high-pressure reactor, and the high-pressure reactor was placed in a forced air drying oven preheated to 170° C., and after reacting for 10 h, it was taken out and naturally cooled to room temperature.
[0056] Step (4) removes solid impurities in the solution by filtering through a filter membrane to obtain a water-soluble indium copper sulfide quantum dot solution.
[0057] Step (5) adding anhydrous ethanol to the water-soluble indium copper sulfide quantum dot solution to generate a precipitate, and drying the precipitate to obtain water-soluble indium copper sulfide quantum dots.
[0058] Example 2 Preparation of water-soluble indium copper sulfide quantum dots
[0059] Step (1) Add 0.0116 g Cu(NO3)2·H2O, 0.0701 g In(NO3)3·xH2O and 0.0913 g CH4N2S into a beaker, add 60 mL deionized water, add 0.2036 g Na2S·9H2O after fully dissolving, so that the molar ratio of copper source, indium source and sulfur source is 1:5:18, and stir evenly to obtain a dark red solution.
[0060] Step (2) The pH of the solution obtained in step (1) was adjusted to 9 with a 0.1 mol / L HCL dilute solution and stirred at room temperature for 30 min.
[0061] Step (3) The solution obtained in step (2) was transferred into a 100 mL high-pressure reactor, and the high-pressure reactor was placed in a forced air drying oven preheated to 170° C., and after reacting for 10 h, it was taken out and naturally cooled to room temperature.
[0062] Step (4) removes solid impurities in the solution by filtering through a filter membrane to obtain a water-soluble indium copper sulfide quantum dot solution.
[0063] Step (5) adding anhydrous ethanol to the water-soluble indium copper sulfide quantum dot solution to generate a precipitate, and drying the precipitate to obtain water-soluble indium copper sulfide quantum dots.
[0064] Example 3 Preparation of water-soluble indium copper sulfide quantum dots
[0065] Step (1) Add 0.011 g Cu(NO3)2·H2O, 0.0772 g In(NO3)3·xH2O and 0.091 g CH4N2S into a beaker, add 60 mL deionized water, add 0.2036 g Na2S·9H2O after fully dissolving, so that the molar ratio of copper source, indium source and sulfur source is 1:5.5:18, and stir evenly to obtain a dark red solution.
[0066] Step (2) The pH of the solution obtained in step (1) was adjusted to 9 with a 0.1 mol / L HCL dilute solution and stirred at room temperature for 30 min.
[0067] Step (3) The solution obtained in step (2) was transferred into a 100 mL high-pressure reactor, and the high-pressure reactor was placed in a forced air drying oven preheated to 170° C., and after reacting for 10 h, it was taken out and naturally cooled to room temperature.
[0068] Step (4) removes solid impurities in the solution by filtering through a filter membrane to obtain a water-soluble indium copper sulfide quantum dot solution.
[0069] Step (5) adding anhydrous ethanol to the water-soluble indium copper sulfide quantum dot solution to generate a precipitate, and drying the precipitate to obtain water-soluble indium copper sulfide quantum dots.
[0070] Example 4 Preparation of Water-Soluble Indium Copper Sulfide Quantum Dots
[0071] Step (1) Add 0.0116 g Cu(NO3)2·H2O, 0.0842 g In(NO3)3·xH2O and 0.0913 g CH4N2S into a beaker, add 60 mL deionized water, add 0.2036 g Na2S·9H2O after fully dissolving, so that the molar ratio of copper source, indium source and sulfur source is 1:6:18, and stir evenly to obtain a dark red solution.
[0072] Step (2) The pH of the solution obtained in step (1) was adjusted to 9 with a 0.1 mol / L HCL dilute solution and stirred at room temperature for 30 min.
[0073] Step (3) The solution obtained in step (2) was transferred into a 100 mL high-pressure reactor, and the high-pressure reactor was placed in a forced air drying oven preheated to 170° C., and after reacting for 10 h, it was taken out and naturally cooled to room temperature.
[0074] Step (4) removes solid impurities in the solution by filtering through a filter membrane to obtain a water-soluble indium copper sulfide quantum dot solution.
[0075] Step (5) adding anhydrous ethanol to the water-soluble indium copper sulfide quantum dot solution to generate a precipitate, and drying the precipitate to obtain water-soluble indium copper sulfide quantum dots.
[0076] Example 5 Preparation of Water-Soluble Indium Copper Sulfide Quantum Dots
[0077] Step (1) Add 0.0116 g Cu(NO3)2·H2O, 0.0912 g In(NO3)3·xH2O and 0.0913 g CH4N2S into a beaker, add 60 mL deionized water, add 0.2036 g Na2S·9H2O after fully dissolving, so that the molar ratio of copper source, indium source and sulfur source is 1:6.5:18, and stir evenly to obtain a dark red solution.
[0078] Step (2) The pH of the solution obtained in step (1) was adjusted to 9 with a 0.1 mol / L HCL dilute solution and stirred at room temperature for 30 min.
[0079] Step (3) The solution obtained in step (2) was transferred into a 100 mL high-pressure reactor, and the high-pressure reactor was placed in a forced air drying oven preheated to 170° C., and after reacting for 10 h, it was taken out and naturally cooled to room temperature.
[0080] Step (4) removes solid impurities in the solution by filtering through a filter membrane to obtain a water-soluble indium copper sulfide quantum dot solution.
[0081] Step (5) adding anhydrous ethanol to the water-soluble indium copper sulfide quantum dot solution to generate a precipitate, and drying the precipitate to obtain water-soluble indium copper sulfide quantum dots.
[0082] Characterization Examples
[0083] See also Figure 2 , Figure 2 The X-ray diffraction patterns (XRD) of CuInS2 quantum dots prepared in Examples 1 to 5 are as follows: Figure 2 It can be seen that when the molar ratio of copper source to indium source is 1:5.5, the crystallinity of CuInS2 quantum dots is the best, and the CuInS2 quantum dots have the highest fluorescence intensity at this time.
[0084] See also Figure 3 , Figure 3 This is a transmission electron microscopy (TEM) image of CuInS2 quantum dots prepared in Example 3. Figure 3 It can be seen that the average particle size of CuInS2 quantum dots is 2.88±0.05nm.
[0085] See also Figure 4 , Figure 4 This is the infrared spectrum of CuInS2 quantum dots prepared in Example 3. After the introduction of thiourea to assist in the synthesis, at 3173 cm -1An absorption peak appeared at , which can be attributed to the stretching vibration of -NH2. The -NH2 functional group of thiourea combined with CuInS2 quantum dots, increasing the stability and dispersibility of the quantum dots, and successfully synthesized CuInS2 quantum dots.
[0086] See also Figure 5 , Figure 5 The X-ray diffraction pattern (XRD) of CuInS2 quantum dots prepared in Example 3. Figure 5 It can be seen that the diffraction peaks appearing at 2θ of 27.78°, 32.38° and 45.82° match the characteristic diffraction peaks of the (112), (004) and (204) crystal planes on the chalcopyrite tetragonal CuInS2 standard card JCPDS:32-0339-CuInS2. The diffraction peaks are consistent with the hexagonal (wurtzite) CuInS2 structure reported by Pan et al. [see D. Pan, L. An, Z. Sun, et al., J. Am. Synthesis of Cu-In-S Ternary Nanocrystals with Tunable Structure and Composition Chem. Soc. 130 (2008) 5620–5621.], and the diffraction peaks at 2θ of 27.44°, 38.54° and 45.56° correspond to the (002), (102) and (110) crystal planes of the simulated wurtzite CuInS2 reported by Pan et al., respectively. This indicates that the synthesized CuInS2 quantum dots are a mixture of two crystal forms of chalcopyrite and wurtzite.
[0087] See also Figure 6 , Figure 6 This is the X-ray photoelectron spectroscopy (XPS) of the CuInS2 quantum dots prepared in Example 3. Figure 6 It can be seen that copper, indium and sulfur all appear in the spectrum, which shows that the quantum dot is composed of three elements: copper, indium and sulfur.
[0088] See also Figure 7 , Figure 7 The UV-visible absorption, excitation and emission spectra of the CuInS2 quantum dots prepared in Example 3 are shown in FIG. Figure 7 It can be seen that CuInS2 quantum dots absorb in the entire visible light region and have a wide absorption spectrum. There is a wide excitation peak at 420nm, a narrow fluorescence emission peak at 650nm, and a wide Stokes shift of 130nm, indicating that the prepared CuInS2 quantum dots exhibit good fluorescence properties.
[0089] in addition, Figure 7The pictures on the upper right side are from left to right the pictures of the CuInS2 quantum dot solution under a fluorescent lamp and under a 365nm ultraviolet lamp. When irradiated with an ultraviolet lamp in a dark box, the CuInS2 quantum dot solution emits a strong orange fluorescence, while when irradiated under a fluorescent lamp, the CuInS2 quantum dot solution appears red and transparent. It can be seen that the CuInS2 quantum dots prepared in Example 3 have good dispersibility and strong fluorescence in aqueous solution.
[0090] Application Example: Application of Indium Copper Sulfide Quantum Dots in Copper Ion Detection
[0091] This embodiment is the application of CuInS2 quantum dot solution in copper ion detection. The CuInS2 quantum dot solution used is the CuInS2 quantum dot solution in Example 3. The steps are as follows:
[0092] (1) In order to explore the effect of CuInS2 quantum dot solution as a fluorescent probe on Cu 2+ The selectivity of Cu 2+ The fluorescence response of CuInS2 quantum dot solution to other metal ions was studied under the same conditions.
[0093] See also Figure 8 , Figure 8 It is a bar graph of the fluorescence intensity ratio F0 / F at the maximum emission wavelength of 468nm after adding different metal ions. Among them, F0 and F are the fluorescence intensity of the solution without metal ions and with metal ions, respectively. It can be seen from the figure that: Cu 2+ The fluorescence quenching degree of CuInS2 quantum dot solution is the strongest. Under the same conditions, adding other metal ion solutions has little effect on the fluorescence intensity, indicating that the CuInS2 quantum dot solution has a strong effect on Cu 2+ Has higher selectivity.
[0094] (2) To explore the presence of other metal ions, the CuInS2 quantum dot solution was used to detect Cu 2+ The interference of CuInS2 quantum dots-Cu 2+ The fluorescence response of the system to the coexistence of other metal ions. Fig. 9 In CuInS2 quantum dots-Cu 2+ The histogram of the fluorescence intensity ratio F0 / F at 468nm after adding different metal ions to the system. Among them, F0 and F are the fluorescence intensity of the solution without metal ions and with metal ions, respectively. It can be seen from the figure that when there are other metal ions and Cu 2+ When they are added to the CuInS2 quantum dot solution at the same time, the degree of fluorescence quenching does not change much, indicating that the presence of other metal ions does not affect the fluorescence quenching of CuInS2 quantum dots. 2+It can be seen that CuInS2 quantum dot solution is used as a fluorescent probe to detect Cu 2+ It shows excellent anti-interference performance.
[0095] (3) Using CuInS2 quantum dot solution as a fluorescent probe to detect Cu 2+
[0096] Take 200 μL of CuInS2 quantum dot solution, pH 7.4, 2800 μL of 0.1 mol / L phosphate buffer solution and different volumes of Cu 2+ solution, add them to 5mL calibration test tubes in turn, and dilute them to the mark with high-purity deionized water to make Cu 2+ The concentration range is 0.2-1.8 μmol / L. Shake well and balance for 30 minutes until the solution is 2+ Then take 2 mL into a cuvette with four sides transparent to light, and use a molecular fluorescence spectrometer to measure the CuInS2 quantum dot solution with different concentrations of Cu added at an excitation wavelength of 468 nm. 2+ The fluorescence intensity, such as Fig.10 As shown in the figure, it can be concluded that the fluorescence intensity of CuInS2 quantum dot solution increases with Cu 2+ The concentration increases and decreases.
[0097] See also Fig.11 , Fig.11 CuInS2 quantum dot solution in different Cu 2+ The line graph of the fluorescence intensity ratio F0 / F at different concentrations, where F0 and F are the fluorescence intensity ratios without Cu 2+ and adding different concentrations of Cu 2+ The fluorescence intensity of the ion solution. It can be seen that the fluorescence intensity ratio F0 / F and Cu 2+ The concentration showed a certain linear relationship. When the linear range was 0.2-1.8 μmol / L, F0 / F and Cu 2+ The concentration relationship is F0 / F=0.46385C Cu 2+ +0.97302 of which R 2 =0.98778, indicating that the fluorescence intensity ratio F0 / F is 2+ The concentration linear relationship is good. The detection limit of this system is calculated to be 23nmol / L.
[0098] The above-described embodiments are only intended to facilitate those skilled in the art to understand the technical solutions of the present invention and are not intended to limit the present invention.
[0099] It should be noted that the technical solution of the present invention has been piloted. After the pilot was completed, a user survey was conducted in a small range. The survey results showed that the user satisfaction was high. At present, preparations for the transformation and promotion of the results have been made. At the same time, a risk warning survey on intellectual property rights was carried out.
Claims
1. A method for preparing water-soluble indium copper sulfide quantum dots, characterized in that: The following steps are involved: (1) adding copper nitrate, indium nitrate and thiourea into a reaction container, adding water into the reaction container, and adding sodium sulfide after the copper nitrate, indium nitrate and thiourea are dissolved, to obtain a first solution; (2) adjusting the pH of the obtained first solution to 7-11 to obtain a second solution, which is then transferred into a reaction kettle; (3) placing the reaction kettle in a preheated air drying oven, reacting at 130-180° C. for 2-12 hours, and naturally cooling to room temperature to obtain a third solution; (4) filtering impurities in the third solution through a filter membrane to obtain an indium copper sulfide quantum dot solution; (5) adding anhydrous ethanol to the indium copper sulfide quantum dot solution to generate a precipitate, and drying the precipitate to obtain indium copper sulfide quantum dots.
2. The method according to claim 1, characterized in that: The molar ratio of the copper nitrate, indium nitrate and sodium sulfide is 1:(4.5-6.5):(15-19).
3. The method according to claim 1, characterized in that The molar ratio of the copper nitrate to thiourea is 1:
25.
4. The method according to claim 1, characterized in that The molar ratio of the copper nitrate, indium nitrate, sodium sulfide and thiourea is 1:5.5:18:
25.
5. The method according to claim 1, characterized in that The pH of the second solution is 9, the reaction temperature of the second solution in the reactor is 170° C., and the reaction time is 10 hours.
6. The method according to claim 1, characterized in that The indium copper sulfide quantum dots have both chalcopyrite and wurtzite crystal forms.
7. An application of indium copper sulfide quantum dots prepared as claimed in any one of claims 1 to 6, characterized in that It is used as a fluorescent probe for copper ion detection.
Citation Information
Patent Citations
Simple and controllable preparation method of copper-indium-sulfur ternary semiconductor nano granules
CN102502788A
Hydro-thermal preparation method for novel near infrared water-soluble copper-indium-sulfur three-element quantum dots
CN102517003A